BESARNYA DEFORMASI YANG DISEBABKAN OLEH TEKANAN TBR (TANDAN BUAH REBUS) TERHADAP POROS BUNCH CRUSHER - Darmadi, Herry; Kurnia, Dian; Malau, Frans Aditiya (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
The research object observed was the amount of deformation caused by the pressure of the TBR (Boiled Fruit Bunches) on the shaft of the bunch crusher. Bunch crusher is a tool that functions to crush loose lumps left in empty bundles by pressing the stacks between two rollers rotating in opposite directions. Operation of a bunch crusher that exceeds its processing capacity and as a result of continuous pressure can cause the shaft of the bunch crusher to experience a deflection which will disrupt the ongoing processing of palm oil. This study aims to determine the magnitude of the bending moment and the magnitude of the deflection in the shaft of the bunch crusher due to the pressure of the boiled fruit bunches. From the day of the research, it was concluded that the bending moment on the bunch crusher shaft when separating the loose fruit bunches from the boiled fruit bunches was 84194,3 kg.mm and the magnitude of the deflection on the bunch crusher shaft due to the TBR (boiled fruit bunches) pressure when separating the loose fruit bunches from the bunches was 0,000155 cm.